Transcriptome analysis of mRNAs, lncRNAs, and miRNAs in the skeletal muscle of Tibetan chickens at different developmental stages - Li, Jie; Chen, Chuwen; Zhao, Ruipeng; Wu, Jinbo; Li, Zhixiong (Frontiers in Physiology, 2023)
As a valuable genetic resource, native birds can contribute to the sustainable development of animal production. Tibetan chicken, known for its special flavor, is one of the important local poultry breeds in Qinghai-Tibet Plateau. However, Tibetan chicken has a slow growth rate and poor carcass traits compared with broilers. Most of the research on Tibetan chicken focused on its hypoxic adaptation, there were fewer studies related to skeletal muscle development. Here, we performed the transcriptional sequencing of leg muscles from Tibetan chicken embryos at E (embryonic)10, E14, and E18. In total, 1,600, 4,610, and 2,166 DE (differentially expressed) mRNAs, 210, 573, and 234 DE lncRNAs (long non-coding RNAs), and 52, 137, and 33 DE miRNAs (microRNAs) were detected between E10 and E14, E10 and E18, and E14 and E18, respectively. Functional prediction showed several DE mRNAs, and the target mRNAs of DE lncRNAs and DE miRNA were significantly enriched in sarcomere organization, actin cytoskeleton organization, myofibril, muscle fiber development, and other terms and pathways related to muscle growth and development. Finally, a lncRNA-miRNA-mRNA ceRNA (competing endogenous RNA) network associated with muscle growth and development, which contained 6 DE lncRNAs, 13 DE miRNAs, and 50 DE mRNAs, were constructed based on the screened DE RNAs by GO enrichment. These DE RNAs possibly play a critical regulatory role in the skeletal muscle development of chicken. The results provide a genomic resource for mRNAs, lncRNAs, and miRNAs potentially involved in the skeletal muscle development of chicken, which lay a foundation for further study of the molecular mechanism of skeletal muscle growth and development in Tibetan chicken.